A Cross-Sectional and Longitudinal Study of Pain among Middle-Aged and Older Adults in Thailand - Supa Pengpid; Karl Peltzer (Pain Research and Management)
Objective. The present study aimed to assess the prevalence and risk factors of pain among ageing adults in Thailand. Methods. Cross-sectional and longitudinal data were analysed from two consecutive national waves of the Health, Aging, and Retirement in Thailand (HART) study in 2015 and 2017. The dependent variable pain was defined as moderate or severe pain in any of the 13 areas of the body over the past month. Independent variables included sociodemographic factors, health risk behaviour, physical and mental health conditions, and healthcare utilization. Results. The baseline or cross-sectional sample consisted of 5,616 participants (≥45 years), and the follow-up or incident sample consisted of 2,305 participants. The proportion of pain in the cross-sectional/baseline sample was 36.0%, and in the incident/follow-up sample 39.9%. In the cross-sectional/baseline multivariable model, poor self-reported mental health, sleep problem, arthritis or rheumatism, brain disease and/or psychiatric problems, lung disease, use of hospital in-patient, conventional out-patient, and traditional medicine practitioners were positively associated with pain. In the incident/follow-up multivariable model, older age, Buddhist religion, class I obesity, poor self-reported mental health, hospital in-patient, private clinic out-patient, and use of a practitioner of traditional medicine were positively associated with pain. Male sex and higher education were negatively associated with both cross-sectional and incident pain. Conclusions. More than one-third of older adults in Thailand had past month moderate or severe pain. Risk factors of pain from cross-sectional and/or incident analysis included older age, female sex, lower education, obesity, poor self-reported mental health, sleep problem, arthritis or rheumatism, brain disease and/or psychiatric problems, lung disease, and conventional and traditional healthcare utilization.